Combating Fake News with the use of Collective Intelligence in Hybrid Systems - Rafal OLSZOWSKI (Communications of International Proceedings, 2021)
The presented study concerns the issue of detecting and combating fake news, that has become more important than ever since the outbreak of the coronavirus pandemic. Only recently, in the scientific literature, there have been attempts to systematize several techniques of detecting FN, taking into account their potential complementarity and proposing to build hybrid systems. The study presents an overview of the scientific literature on this topic. In addition, a qualitative empirical research based on expert interviews was presented. This research highlighted the significant role of Collective Intelligence technique in the proposed type of hybrid systems.
Keywords: Fake News; Collective Intelligence; Hybrid System